2011
DOI: 10.1007/s00296-011-1820-3
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of arthritis in India and Pakistan: a review

Abstract: Recent studies of rheumatoid arthritis worldwide suggest that prevalence of arthritis is higher in Europe and North America than in developing countries. Prevalence data for major arthritis disorders have been compiled in West for several decades, but figures from the third world are just emerging. A coordinated effort by WHO and ILAR (International League Against Rheumatism) has resulted in collecting data for countries like Philippines, China, Malaysia, Indonesia, and rural South Africa but the information a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 19 publications
0
35
1
3
Order By: Relevance
“…Epidemiological studies have reported a wide variance in different regions of the world, with low rates in Asian populations14,15 and relatively higher frequencies in those of European descent 16,17. Vast differences also appear within the same country as demonstrated by polyarticular disease occurring more frequently in southern India as compared to the northern region 18. Considering all subtypes of arthritis, the incidence of childhood arthritis ranges from 0.83 per 100,000 children in Japan14 to 23 per 100,000 in Norway 19.…”
Section: Epidemiologymentioning
confidence: 99%
“…Epidemiological studies have reported a wide variance in different regions of the world, with low rates in Asian populations14,15 and relatively higher frequencies in those of European descent 16,17. Vast differences also appear within the same country as demonstrated by polyarticular disease occurring more frequently in southern India as compared to the northern region 18. Considering all subtypes of arthritis, the incidence of childhood arthritis ranges from 0.83 per 100,000 children in Japan14 to 23 per 100,000 in Norway 19.…”
Section: Epidemiologymentioning
confidence: 99%
“…In developing countries (Oman, China, Argentina, Yugoslavia), the prevalence was lower, ranging from 1.8 per 1000 in the former country of Yugoslavia to 3.6 per 1000 in Oman. In a comparison of RA in India and in Pakistan by Akhter et al ., the prevalence of RA in Pakistan (5/1000) fell within the range presented for India (2/1000 through 10/1000). In the studies we present, the RA prevalence, based on the ACR criteria, ranged from 2.8 per 1000 to seven per 1000, suggesting that prevalence may vary throughout India as much as it varies throughout Europe and could be comparable to prevalence in the Western world.…”
Section: Discussionmentioning
confidence: 71%
“…Rheumatoid arthritis (RA) is a chronic inflammatory systemic disease exhibiting clinical signs and symptoms of predominantly joint disease [1][2][3]. This disease is characterized by symmetrical bilateral involvement of mostly small joints of hand and feet; however as it leads to chronic synovitis, all joints may be involved [4][5].…”
Section: Introductionmentioning
confidence: 99%